Effects of dietary supplementation of combined safflower meal and sunflower meal on fattening performance and carcass quality characteristics in quails - Tuba Bulbul; Elmas Ulutas; Vural Ozdemir; Aziz Bulbul; Mustafa Evcimen (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out to determine the effects of combined safflower-sunflower meal (SSM) supplementation in quail diets on fattening performance and some carcass quality parameters. Materials and Methods: A total of 300 three-day-old Japanese quails (Coturnix coturnix japonica), including both males and females were divided into one control group and four treatment groups containing 60 quails in each. Each group was sub-divided into five replicates each containing 12 quails. The control group was fed corn-soybean meal based diet without SSM. The SSM was used at level of 10% (SSM10), 20% (SSM20), 30% (SSM30) and 40% (SSM40) in treatment diets (in each treatment S and SF ratio is 1:1). The experimental period was lasted for 5 weeks. Results: There were no changes in terms of body weights, body weight gain and feed intake as well as carcass weights, relative weight of liver, heart, spleen, gizzard, proventriculus and abdominal fat in all experimental groups with SSM supplementation (P>0.05). Feed conversion ratio impaired in the SSM40 group compared with the control and the other groups (P<0.001). Conclusions: It may be stated that the supplementation of safflower-sunflower meal (C:S, 1:1) in combination to diets has no any adverse effect on the some performance and carcass quality characteristics, and as well as the supplementation of up to 30% of these might be more effective on feed conversion ratio in quails.